Literasi Teknologi Dan Sistem Informasi Bagi Remaja Pemuda GMIM Syalom Kolongan Atas Sonder: Technology and Information Systems literacy For Young People GMIM Shalom Kolongan Atas Sonder (Tumou Tou: Jurnal Pengabdian Masyarakat, 2024)
Today's human existence is in the digital era which is characterized by the massive use of gadgets based on information technology. The majority of teenagers and church youth have gadgets, but in general they only use them as a means of entertainment on social media. In fact, gadgets can be used for something productive such as doing online business. To provide insight and understanding to partners in using Gadgets productively, the PKM team shares practical information about Gadgets to capture business opportunities conducted online. This activity is carried out using a lecture method based on adult learning. The results of the activity provide information that the majority of participants feel it is important to understand technology and information systems. Participants generally feel the need to increase their knowledge in the field of information technology. 66.7% of participants have an interest in utilizing information technology for business, and more than 70% are aware of online business marketplaces. As much 77.8% are interested in using the gadgets they own for online business, but only 55.6% are interested in becoming entrepreneurs, however, there are 74.1% who are thinking about creating products that come from existing resources in the environment where they live. The majority of participants in this activity felt it was important to understand technology and information systems related to digital business.